2022
DOI: 10.1051/0004-6361/202243441
|View full text |Cite
|
Sign up to set email alerts
|

Eclipse of the V773 Tau B circumbinary disc

Abstract: Context. Young multiple stellar systems can host both circumstellar and circumbinary disks composed of gas and dust, and the orientations of circumbinary disks can be sculpted by the orientation and eccentricity of the central binaries. Studying multiple binary systems and their associated disks enables understanding of the size and distribution of the planetary systems that subsequently form around them. Aims. A deep (∼ 70%) and extended (∼150 days) eclipse was seen towards the young multiple stellar system V… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…Depending on the binary and disk parameters, the alignment timescale can be longer than the disk lifetime, and so the planetesimal disk may form in a misaligned disk. We note that the two currently observed polar circumbinary gas disks have external companions (Kennedy et al 2019;Kenworthy et al 2022) that truncate the outer part of the circumbinary disk, leading to a radially narrow disk and a short alignment timescale (Martin et al 2022). The timescale for gas disk alignment also depends upon a number of other binary and disk parameters including the binary semimajor axis, binary eccentricity, disk viscosity, and disk temperature (e.g., .…”
Section: Formation Of Interstellar Asteroidsmentioning
confidence: 94%
See 1 more Smart Citation
“…Depending on the binary and disk parameters, the alignment timescale can be longer than the disk lifetime, and so the planetesimal disk may form in a misaligned disk. We note that the two currently observed polar circumbinary gas disks have external companions (Kennedy et al 2019;Kenworthy et al 2022) that truncate the outer part of the circumbinary disk, leading to a radially narrow disk and a short alignment timescale (Martin et al 2022). The timescale for gas disk alignment also depends upon a number of other binary and disk parameters including the binary semimajor axis, binary eccentricity, disk viscosity, and disk temperature (e.g., .…”
Section: Formation Of Interstellar Asteroidsmentioning
confidence: 94%
“…Circumbinary gas disks (CBDs) with large misalignments relative to the binary orbital plane are commonly observed in nature (e.g., Chiang & Murray-Clay 2004;Köhler 2011;Andrews et al 2014;Brinch et al 2016;Takakuwa et al 2017;Fang et al 2019;Kennedy et al 2019;Kenworthy et al 2022;Zhu et al 2022). The degree of CBD misalignment often increases with binary separation and eccentricity (Czekala et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Dissipation in the disk leads to alignment either toward coplanar (Facchini et al 2013;Nixon et al 2013) or polar, depending on the initial tilt (Martin & Lubow 2017;Zanazzi & Lai 2018;Cuello & Giuppone 2019). Several polar circumbinary disks around eccentric binaries have been observed (Kennedy et al 2012(Kennedy et al , 2019Kenworthy et al 2022) although none have yet been observed around a triple star. While polar circumbinary planets have not yet been observed, their formation may be as efficient as in a coplanar configuration (Childs & Martin 2021a, 2021b.…”
Section: Introductionmentioning
confidence: 99%
“…Based on considerations of disk evolution, if it is sufficiently fast, then we expect planets to be either coplanar or polar with respect to the binary orbit (e.g., Martin & Lubow 2017). While polar planets have not yet been found, there are several examples of polar disks (Kennedy et al 2012(Kennedy et al , 2019Kenworthy et al 2022).…”
Section: Introductionmentioning
confidence: 99%